Algeria : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
In this study, the following are represented in the form of tabulation: basic economic and financial indicators, supply and usage of resources, sectoral distribution of GDP, production, exports, and consumption of liquid petroleum products, domestic prices of major energy products, agricultural and land use patterns, crop yields, indices of industrial production, production of minerals, housing supply, consumer index, household supply, central government revenue, expenditure, and monetary survey, hydrocarbon exports, and trade indices. They are listed based on statistical information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet